Reformasi Konstitusi dan Dinamika Penegakan Hak Asasi Manusia di Indonesia - Darmawan, Iqbal Panji (Media Hukum Indonesia (MHI), 2026)
The constitution plays a fundamental role in a country's legal and governmental system as the supreme basic law governing institutional structures, limitations on power, and the protection of human rights and fundamental freedoms. In Indonesia, the 1945 Constitution guarantees the fundamental rights of citizens and serves as the foundation of the rule of law, ensuring justice and non-discrimination. However, the implementation of the constitution faces various challenges, particularly during the Reformation era, including weak law enforcement, a culture of impunity, corruption, and political intervention in law enforcement agencies. Despite progress in pro-human rights legal instruments and the active role of civil society, regulatory barriers and contemporary political dynamics still hinder the effective protection of human rights. This study highlights the importance of a sustained commitment from the government, civil society, and legal institutions to translate constitutional principles into practice, so that human rights and social justice can be effectively realized in Indonesia..budaya lokal, dan keterbatasan akses terhadap pencatatan resmi.